2005
DOI: 10.1002/ange.200461444
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Cross‐Coupling Reactions of Aryl Sulfonates and Phosphates through Photoheterolysis of Aryl–Oxygen Bonds

Abstract: Die photochemische Spaltung von Ar‐O‐Bindungen in Phenylestern mit elektronenreichen Substituenten lässt sich sehr gut für die Arylierung von Alkenen und Arenen nutzen. Die nach einem SN1‐Mechanismus über ein Triplett‐Phenylkation verlaufende Reaktion liefert unter milden Bedingungen Allylbenzol‐ bzw. Biphenylderivate (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…A radically different approach for the synthesis of aryl acetylenes is presented here, and is based on the use of phenyl cations. In the last few years we have demonstrated that these intermediates (in the triplet state) are obtained smoothly by photolysis of aryl halides substitued with electron‐donating groups (for example, chlorophenol15 or fluoroanilines16), aryl sulfonates, and aryl phosphates (for example, methoxyphenyl mesylate or N , N ‐dimethylaminophenyl phosphate),17 and add to alkenes to form an arylC bond via a phenonium ion 15a. 18 We surmised that phenyl cations would react with triple bonds to yield β‐phenylvinyl cations, or more probably cyclic vinylenebenzenium ions (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…A radically different approach for the synthesis of aryl acetylenes is presented here, and is based on the use of phenyl cations. In the last few years we have demonstrated that these intermediates (in the triplet state) are obtained smoothly by photolysis of aryl halides substitued with electron‐donating groups (for example, chlorophenol15 or fluoroanilines16), aryl sulfonates, and aryl phosphates (for example, methoxyphenyl mesylate or N , N ‐dimethylaminophenyl phosphate),17 and add to alkenes to form an arylC bond via a phenonium ion 15a. 18 We surmised that phenyl cations would react with triple bonds to yield β‐phenylvinyl cations, or more probably cyclic vinylenebenzenium ions (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…[27] Another "innocent" anion was PF 6 À , [6b] but the high viscosity of 2 b hampered an efficient arylation reaction. As for the mesylate anion, its coupling with phenyl cation may go undetected, since 4-aminophenylmesylate undergo itself photoheterolysis [28] leading back to the cation. At any rate, no mesylate was detected.…”
Section: ) Photolysis Of 1 Was Effective In Ils Previous Work Hadmentioning
confidence: 96%
“…EPR spectra of the phenyl cation have been obtained by photolysis of some phenyl diazonium ions in EtOH at 77 K, [8] and only recently, the IR spectrum of the phenyl cation was obtained by photolysis of phenyl iodide in an argon matrix at 4 K in which the phenyl radical is formed and gives the cation by ensuing electron transfer. [9] Recently, a class of reactions has emerged in which C À C bond formation has been achieved by the photolysis of electron-donating substituted aryl halides [10] or esters [11] in the presence of carbon nucleophiles, for example, alkenes, alkynes, or (hetero)aromatics, with little competing solvolysis. These reactions have been rationalized in terms of trapping of the triplet phenylium ion (I, Scheme 1), which generates further cationic intermediates, for example, the phenonium ion (the cyclopropanespirocyclohexadienyl cation, II) in the case of alkenes.…”
Section: Abstract: Aryl Cations · Carbo-a C H T U N G T R E N N U N Gmentioning
confidence: 99%